2019
DOI: 10.1039/c8dt04317e
|View full text |Cite|
|
Sign up to set email alerts
|

Luminescent Nd2S3 thin films: a new chemical vapour deposition route towards rare-earth sulphides

Abstract: Development of two new neodymium containing precursors and their successful implementation in the MOCVD of luminescent Nd2S3 thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 87 publications
1
14
0
2
Order By: Relevance
“…The guanidinates seem to decompose into smaller fragments, indicated by the peak with 100 % intensity which is observed for fragments associated with the organic ligands and their decomposition fragments. A similar fragmentation behavior is observed for the literature known rare‐earth tris guanidinates [24, 40] and tris‐amidinates [40a, 41] complexes.…”
Section: Resultssupporting
confidence: 88%
“…The guanidinates seem to decompose into smaller fragments, indicated by the peak with 100 % intensity which is observed for fragments associated with the organic ligands and their decomposition fragments. A similar fragmentation behavior is observed for the literature known rare‐earth tris guanidinates [24, 40] and tris‐amidinates [40a, 41] complexes.…”
Section: Resultssupporting
confidence: 88%
“…Devi等 [73] 开发了两种CVD前驱体Nd(Dpdmg) 3 和 前驱体热分解法是在溶液中、真空条件或N 2 /Ar 气氛中热解含硫前体, 如镧系二硫代氨基甲酸盐配合 物或镧系硫醇酸盐, 从而获得稀土硫化物的方法 [76] . 的分子结构及γ-Nd 2 S 3 薄膜光致发光示意图 [73] ; (b) α-Sm 2 S 3 纳 米线薄膜合成实验装置示意图 [74] (网络版彩图) 末状Ln 2 S 3 , 但由于前驱体分解后易存在碳杂质, 因而 产物纯度易受到影响 [76,77] . Larionov等 [78] 讨论了镧系 元素1,1-二硫代盐配合物的合成、结构与性质, 及其 作为前驱体合成稀土硫化物的实验结果, 如通过…”
Section: 气相合成方法unclassified
“…The RECs in the form of the host part of the thin films or wires have exhibited fascinating performances in optical and electrical applications by virtue of their unique crystal and electronic structures . As the main part of the materials, the RECs are generally polycrystalline, typically fall in the categories of α‐phase of orthorhombic LaF 3 ‐type structure (Pnma) and γ‐phase of Th 3 P 4 ‐type with plenty of defects, whose band gaps are 1.74 to 1.88 eV and 2.55 to 2.74 eV, respectively . Therefore, to obtain the RECs of low‐dimensional scale with refined structure and property, various dry synthesis approaches have been reported, including metal‐organic chemical vapor deposition (MOCVD), sputtering, pulse laser deposition (PLD) and molecular beam epitaxy (MBE) methods.…”
Section: Materials Classification and Synthesismentioning
confidence: 99%
“…Therefore, various new metal‐organic complexes have been exploited as the precursors of RECs. Devi et al reported that they prepared the Nd 2 S 3 films using two new Nd precursors, namely, Nd(dpdmg) 3 and Nd(dpamd) 3 . It was noted that the thickness and growth rate of the films were greatly affected by the precursors.…”
Section: Materials Classification and Synthesismentioning
confidence: 99%
See 1 more Smart Citation